2017
DOI: 10.1038/s41598-017-12751-3
|View full text |Cite
|
Sign up to set email alerts
|

A Point-based Mortality Prediction System for Older Adults with Diabetes

Abstract: The mortality prediction models for the general diabetic population have been well established, but the corresponding elderly-specific model is still lacking. This study aims to develop a mortality prediction model for the elderly with diabetes. The data used for model establishment were derived from the nationwide adult health screening program in Taiwan in 2007–2010, from which we applied a 10-fold cross-validation method for model construction and internal validation. The external validation was tested on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 46 publications
0
9
0
1
Order By: Relevance
“…A study [ 28 ] found that a higher WBC count was a predictor of death in DM patients with heart failure. A higher WBC count was associated with an increased risk of death in T2DM patients [ 29 ]. Our model showed that WBC count was a significant independent risk prognostic factor for T2DM patients with AKI.…”
Section: Discussionmentioning
confidence: 99%
“…A study [ 28 ] found that a higher WBC count was a predictor of death in DM patients with heart failure. A higher WBC count was associated with an increased risk of death in T2DM patients [ 29 ]. Our model showed that WBC count was a significant independent risk prognostic factor for T2DM patients with AKI.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are consistent with the literature regarding the significance of components in the both axes for predicting lifestyle-related chronic diseases and their outcomes. It was reported that the significant predictor variables for mortality in older adults with diabetes included age, gender, smoking status, BMI, fasting glucose, WBC, and GPT [ 23 ]. A role of smoking status was also shown in predicting mortality outcomes, in particular for cardiovascular mortality [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several models have been developed to predict all-cause mortality as the ultimate complication of diabetes. Models that have been externally validated include the RECODe model, the model by Chang et al and the ENFORCE model [14,60,61]. The included predictors were mainly demographic, BPor blood lipid-related, or were renal variables (Table 3 and ESM Table 1).…”
Section: Risk Models For the Prediction Of All-cause Mortalitymentioning
confidence: 99%
“…The included predictors were mainly demographic, BPor blood lipid-related, or were renal variables (Table 3 and ESM Table 1). All three models showed acceptable to good discrimination in the external validations, with C statistics of 0.71-0.81 (RECODe), 0.75-0.82 (ENFORCE) and 0.69 (Chang et al) [14,[60][61][62][63]. For the prediction of mortality in type 1 diabetes, few models exist and are set mainly in the context of lifetime health outcome simulations [64].…”
Section: Risk Models For the Prediction Of All-cause Mortalitymentioning
confidence: 99%